Comparative analysis of oral health behaviour and utilisation of oral health care services in the general population and among patients with non-communicable diseases in Korea: a repeated cross-sectional survey conducted from 2008 to 2022 - Jeehee Pyo; Hyeran Jeong; Noor Afif Mahmudah; Young-Kwon Park; Minsu Ock (PLoS ONE, 2025)
Background Understanding the oral health behaviour and utilisation of oral health care services among patients with non-communicable diseases (NCDs) is essential for the development of oral health care management services for these patients. In this study, we comparatively analysed the trends in oral health behaviour and oral health care service utilisation among patients with various NCDs and the general population. Methods We analysed data obtained via the Korea Community Health Survey from 2008 to 2022. Comparative analyses of the general population and patients with 15 different NCDs, including diabetes mellitus and depression, were conducted for the following variables: toothbrushing practice, use of dental floss and interdental brushes, annual scaling (tartar removal), and annual oral examinations. Joinpoint regression analyses were used to assess for statistically significant changes in oral health behaviour and oral health care service utilisation according to year and region. Results Overall, oral health behaviour steadily improved in the general population and among patients with NCDs. However, the rates of toothbrushing before going to bed in patients with hypertension (90.0%) and diabetes mellitus (88.7%) were still lower than that in the general population (92.9%) in 2022. Regarding oral health service utilisation, the rates of annual scaling and oral examination among patients with NCDs, apart from those with dyslipidaemia, were lower than those in the general population. For example, in 2017, the rates of annual scaling and oral examination of patients with diabetes mellitus were 43.4% and 36.5%, respectively. These rates were lower than those in the general population, at 47.2% and 43.0%, respectively. In terms of inter-regional variations in oral health-related indicators, considerable inter-regional variations were observed in the oral health behaviour and oral health care service utilisation of patients with NCDs. Conclusion This study highlighted that the practice and utilisation rates of oral health behaviour and oral health care services, respectively, among patients with NCDs have increased. However, in comparison with those of the general population, further improvements are necessary. A practical solution could be to establish a system that provides all necessary oral-related services, such as patient education and oral examinations, to NCDs patients through medical-dental integration or oral medical care coordination.